How to deal with so-called “vowel verbs with variant non-vowel forms” in a bilingual Zulu lexicon? The case for a pragmatic approach. (Journal of the Digital Humanities Association of Southern Africa (DHASA), 2023)
Whilst lemmatisation in Zulu (and cognate languages) remains to this day a partially unsettled issue, with dictionaries, both bilingual and monolingual, adopting differing strategies in respect of nouns, we wish to focus here on a somewhat minute aspect of the matter: how to lemmatize verbs with optional initial vowels. As the variation occurs at the initial, it is crucial that it receives proper dictionary treatment, lest the user be misdirected or misinformed.
Keywords: isiZulu; lexicography; vowel verbs